HgCdTe Heterostructures Grown by MBE on Si(310) for Infrared Photodetectors - Yakushev, Maxim; Varavin, Vasily.; Vasilyev, Vladimir; Dvoretsky, Sergey; Sabinina, Irina; Sidorov, Yuri.; Sorochkin, Aleksandr; Aseev, Aleksandr (IntechOpen, 2011)
None